Mass variations in the Siberian permafrost region based on new GRACE results and auxiliary modeling - Shabanloui, Akbar; Müller, Jürgen (2014)
GRACE (Gravity Recovery and Climate Experiment) determines the integral mass variations in the Earth system with different spatial-temporal resolution. These mass variations should be adequately separated for better understanding of the single signal contributions. In Siberia, the temporal mass variations are related to hydrological processes including thawing of huge permafrost layers. The permafrost layers with different thicknesses cover about 80% of Siberia. Therefore these frozen sheets play an important role for sea level rise and the hydrological water cycle. In this study, the integral mass variations in Siberia are precisely estimated based on the new release of GRACE from GFZ (RL05a). On the other hand, various hydrological contributions (lake level variation, river runoff, etc.) can be estimated from different models and specific data. Here, mass variations in the Siberian permafrost region based on GRACE results and different hydrological models/data will be jointly investigated.